Placental Morphologic Similarities Between ZIKV-Positive and HIV-Positive Pregnant Women - Martins Ronchi, Daiane Cristine; Scaranello Malaquias, Mineia Alessandra; Rebutini, Patrícia Zadorosnei; Panini do Carmo, Letícia Arianne; Neto, Plínio Cézar; Marini, Emily Scaranello; Prokopenko, Amanda; Nagashima, Seigo; Zanluca, Camila; Duarte dos Santos, Claudia Nunes; de Noronha, Lúcia (Frontiers in Immunology, 2021)
Zika virus (ZIKV) caused global concern due to Brazil's unexpected epidemic, and it was associated with congenital microcephaly and other gestational intercurrences. The study aimed to analyze the placenta morphometric changes of ZIKV-infected pregnant women (ZIKV group; n = 23) compared to placentas of HIV-infected (HIV group; n = 24) and healthy pregnant women (N-control group; n = 22). It also analyzed the relationship between the morphometric results and pathological alterations on conventional microscopy, gestational trimester of infection, and presence of the Congenital Zika Syndrome (CZS). There was a significant increase in area (p = 0.0172), as well as a higher number of knots (p = 0.0027), sprouts (p < 0.0001), and CD163 +Hofbauer cells (HCs) (p < 0.0001) in the ZIKV group compared to the N-control group, suggesting that villous dysmaturity and HCs hyperplasia could be associated with ZIKV infections. The HIV group had a higher area (p < 0.0001), perimeter (p = 0.0001), sprouts (p < 0.0001) and CD163 + HCs (p < 0.0001) compared to the N-control group, demonstrating that the morphometric abnormalities found in the ZIKV and HIV group are probably similar. However, when ZIKV and HIV groups are compared, it was observed a higher number of sprouts (p = 0.0066) and CD163+ HCs (p < 0.0001) in the first one, suggesting that placental ZIKV congenital changes could be more pronounced.